2018
DOI: 10.5267/j.ijiec.2017.9.001
|View full text |Cite
|
Sign up to set email alerts
|

Harvesting and transport operations to optimise biomass supply chain and industrial biorefinery processes

Abstract: In Australia, Bioenergy plays an important role in modern power systems, where many biomass resources provide greenhouse gas neutral and electricity at a variety of scales. By 2050, the Biomass energy is projected to have a 40-50 % share as an alternative source of energy. In addition to conversion of biomass, barriers and uncertainties in the production, supply may hinder biomass energy development. The sugarcane is an essential ingredient in the production of Bioenergy, across the whole spectrum ranging from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 6 publications
0
6
0
2
Order By: Relevance
“…After the data is written, the second authentication is to use the data of the first authentication to perform the second authentication when interacting between blocks (gateway nodes). Take out the relevant information and necessary cryptographic data of the other party from the blockchain, and then you can carry out secure data interaction [27].…”
Section: Authentication Interaction Based On New Blocksmentioning
confidence: 99%
“…After the data is written, the second authentication is to use the data of the first authentication to perform the second authentication when interacting between blocks (gateway nodes). Take out the relevant information and necessary cryptographic data of the other party from the blockchain, and then you can carry out secure data interaction [27].…”
Section: Authentication Interaction Based On New Blocksmentioning
confidence: 99%
“…Assuming the power plant technology as fixed-bed (grate) combustion, the technology basically works by burning biomass directly to produce steam that turns a turbine to drive a generator, thus producing electricity [18]. Energy potentials of the residues are calculated by Equation ( 2) [16,[20][21][22]24], available residue amounts, and calorific values are provided in the literature (Table 2).…”
Section: Calculations Of Available Biomass and Corresponding Energy A...mentioning
confidence: 99%
“…Quantify the potential energy that could be produced by food crops and trees; [18] investigated the supply chain system of Australia and concluded that transporting and collection periods have a high impact on the optimization of a healthy bioenergy production system, which is an advantage for Texas in terms of locations of delivery end points. Studies on determining biomass potential and revealing usage possibilities based on the values obtained through compilation studies have also been published in reputable journals.…”
mentioning
confidence: 99%
“…Por su parte Matindi et al (2018), estudiaron la incertidumbre en los rendimientos de campo en las operaciones de cosecha y transporte de caña de azúcar, las cuales son necesarias para la producción de biocombustibles y energía eléctrica; para resolver el problema planteado, se utilizó un enfoque híbrido entre simulación y metaheurísticas como método de solución.…”
Section: Fuentes De Incertidumbre En La Asc De La Caña De Azúcar Y La...unclassified